Pengaruh Tingkat Bagi Hasil Dan Komunikasi Pemasaran Terpadu (Integrated Marketing Communication) Terhadap Keputusan Nasabah Untuk Menabung Pada Bank Muamalat Indonesia Cabang Semarang - Sumarlina, Sumarlina; Rodhiyah, Rodhiyah; Saryadi, Saryadi (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2014)
Today the growth of Islamic banking services is growing in Indonesia. Bank Muamalat Indonesia as a provider of Sharia-compliant banking services in Indonesia seeks to meet the needs of its customers with a wide range of attractive savings products. The aim of the research is to find out the influence of the profit-sharing and integrated marketing communication to customers for savings. The population this research is all of our customers Bank Muamalat Indonesia branch Semarang, with 100 respondents as sample. The type of this research is explanatory research with primary data collection through questionnaires using purposive sampling technique.Analysis techniques used linier regression with SPSS version 15. Results of research partially shows the extent influence the profit-sharing against the ruling customers of 51.6 percent, test result T 10.230 > 1.9845, and a simple regression Y = 12.823 1.807 X1. There is a degree of influence to the profit-sharing of the decision of the customer to saving. While integrated marketing communications to customers of 52.1 percent, test result T 10.315 > 1.9845 and a simple regression Y = 5.061 0.590 X2. There is a degree of integrated marketing communication to customers for savings. Simultaneously great the influence high for the result and integrated marketing communications to customers of 61.8 percent, test result F 78.398 > 3.09 and multiple regression Y = 4.178 1.067 X1 0.354 X2. There is a degree of the profit-sharing and integrated marketing communication to customers for savings. Based on the results of the study concluded the level of profit-sharing and integrated marketing communications has a positive and significant influence on the decision of the customer to save money. Researchers suggest that Bank Muamalat Indonesia Semarang branch remains stabilize for a given outcome, improving performance public relations and optimize facilities car around to make it more closely with our customers.